Transcriptome Analyses Reveal Candidate Genes Potentially Involved in Al Stress Response in Alfalfa - Liu, Wenxian; Xiong, Conghui; Yan, Longfeng; Zhang, Zhengshe; Ma, Lichao; Wang, Yanrong; Liu, Yajie; Liu, Zhipeng (Frontiers in Plant Science, 2017)
Alfalfa is the most extensively cultivated forage legume, yet most alfalfa cultivars are not aluminum tolerant, and the molecular mechanisms underlying alfalfa responses to Al stress are largely unknown. In this study, we aimed to understand how alfalfa responds to Al stress by identifying and analyzing Al-stress-responsive genes in alfalfa roots at the whole-genome scale. The transcriptome changes in alfalfa roots under Al stress for 4, 8, or 24 h were analyzed using Illumina high-throughput sequencing platforms. A total of 2464 differentially expressed genes (DEGs) were identified, and most were up-regulated at early (4 h) and/or late (24 h) Al exposure time points rather than at the middle exposure time point (8 h). Metabolic pathway enrichment analysis demonstrated that the DEGs involved in ribosome, protein biosynthesis, and process, the citrate cycle, membrane transport, and hormonal regulation were preferentially enriched and regulated. Biosynthesis inhibition and signal transduction downstream of auxin- and ethylene-mediated signals occur during alfalfa responses to root growth inhibition. The internal Al detoxification mechanisms play important roles in alfalfa roots under Al stress. These findings provide valuable information for identifying and characterizing important components in the Al signaling network in alfalfa and enhance understanding of the molecular mechanisms underlying alfalfa responses to Al stress.